2001
DOI: 10.1137/s0036141099358300
|View full text |Cite
|
Sign up to set email alerts
|

Travelling Waves for Fourth Order Parabolic Equations

Abstract: Abstract. We study travelling wave solutions for a class of fourth order parabolic equations. Travelling wave fronts of the form u(x, t) = U (x + ct), connecting homogeneous states, are proven to exist in various cases: connections between two stable states, as well as connections between an unstable and a stable state, are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Our work extends that of [3] in several ways. First of all, we consider a general class of nonlinear terms and we develop a geometrical proof of the existence of these fronts as opposed to the variational approach in [3]. More importantly, we also analyse the nonlinear stability of these fronts which does not yet appear to have been discussed.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our work extends that of [3] in several ways. First of all, we consider a general class of nonlinear terms and we develop a geometrical proof of the existence of these fronts as opposed to the variational approach in [3]. More importantly, we also analyse the nonlinear stability of these fronts which does not yet appear to have been discussed.…”
Section: Introductionsupporting
confidence: 56%
“…Also, periodic solutions , solitons (homoclinic/heteroclinic orbits) and chaotic patterns have been studied for the stationary part of this equation, see [20,26]. For the nonlinearity N=a(1 − B 2 ) − B 3 (0 < a < 1) the existence of traveling waves connecting B= ± 1 has been studied in [1,3]. Finally, in [3] it is also shown that for N(B)=−B 2 there exists a traveling wave from B=1 to B=0 for every positive wavespeed and D ¥ R.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such orbits have also been found in four-dimensional systems where the primary homoclinic orbit converges to a center with non-semisimple eigenvalues on the imaginary axis [43] and in systems that have two primary homoclinic orbits to the same saddle equilibrium [39]. In [378,407,409], variational methods were used to find multibump orbits in the Swift-Hohenberg equation.…”
Section: Variational Methodsmentioning
confidence: 99%